2011
DOI: 10.1097/scs.0b013e318208542e
|View full text |Cite
|
Sign up to set email alerts
|

Intraorbital Isolated Mucocele

Abstract: A 55-year-old man was presented with an orbital mass. The magnetic resonance imaging revealed that the dimensions of the mass were 29×19×17 mm. The most probable diagnosis with the magnetic resonance imaging findings was dermoid cyst. The mass was a cyst and marsupialized by functional endonasal endoscopic sinus surgery without any complication. Intraoperative findings of the mass were thought to be a hydatid cyst, but the diagnostic tests were negative, and the pathologic result was consistent with mucocele.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Isolated orbital mucocele has been reported by Baysal et al 5 . A 55-year-old man was diagnosed with left isolated orbital mucocele without a history of trauma or obstruction of paranasal sinus.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Isolated orbital mucocele has been reported by Baysal et al 5 . A 55-year-old man was diagnosed with left isolated orbital mucocele without a history of trauma or obstruction of paranasal sinus.…”
Section: Discussionmentioning
confidence: 86%
“…The contributing factor for orbital mucocele can be chronic sinusitis, nasal polyp, orbital wall fracture, post open or endoscopic surgery, and congenital effects. It has been postulated that isolated orbital mucocele can occur due to islands of sinus tissue within the orbit that developed from embryological tissue or after trauma 5 . Thus, the island of sinus tissues will proliferate into the cystic lesion within the orbital cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, endoscopic sinus surgery has been favored over the direct orbital approach for its safety and efficacy in treating mucoceles with a lower morbidity, reduced hospital stay, and reduced mucocele recurrent rate 9,10 . Bysal et al 4 reported that an isolated orbital mucocele in medial orbit was successfully managed by endoscopic intranasal marsupialization. In the case of the isolated intraorbital mucocele in inferior orbit, similar with our case, Jung, et al 5 treated it by enucleation of the mucocele using transantral approach, however, we treated it successfully by endoscopic intranasal marsupialization without any complications including those of external approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Mucocele is typically seen as a cystic mass with non-contrast enhanced soft tissue density and clear margin in computed tomography (CT) 1,3 . In T1-weighted imaging series of magnetic resonance (MR) image, the lesion has intermediate or low signal intensity without gadolinium enhancement and high signal intensity in T2-weighted series 3,4 . Although the treatment choice of isolated intraorbital mucocele has not been established because of the rarity of the disease, some authors suggest that the optimum treatment is the complete removal of the mucocele to exclude the possibility of recurrence from remnant mucosa 1,2,5,6 .…”
mentioning
confidence: 99%
See 1 more Smart Citation